2020
DOI: 10.3390/ani10091658
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulator YqeI, Locating at ETT2 Locus, Affects the Pathogenicity of Avian Pathogenic Escherichia coli

Abstract: Avian pathogenic Escherichia coli (APEC) is the leading cause of systemic infections in poultry worldwide and has a hidden threat to public health. Escherichia coli type three secretion system 2 (ETT2), similar to the Salmonella pathogenicity island SPI1, is widely distributed in APEC and associated with virulence. The function of YqeI, which is one of the hypothetical transcriptional regulators locating at the ETT2 locus of APEC, is unknown. In this study, we successfully obtained the mutant strain AE81ΔyqeI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Among the different bacterial secretion systems, two secretion systems (type III and VI) contribute to APEC pathogenesis [ 11 , 12 ]. The regulators (EtrA and YqeI) [ 12 , 78 ] and ATPase (EivC) [ 79 ] of the type III secretion system 2 (ETT2) play a role in motility, adhesion, intracellular survival, proliferation, colonization, resistance to phagocytosis and serum bactericidal activity, expression of fimbriae genes, and the downregulation of pro-inflammatory cytokine responses. Similarly, different components of type VI secretion system, DotU (organelle trafficking protein), IcmF (intracellular multiplication factor), Hcp (hemolysis co-regulation protein), CpxR, CpxA (envelope stress response system), ClpV (ATPase), and VrgG (secreted protein) mediate interbacterial competition, adhesion, invasion, intracellular survival, colonization, motility, biofilm formation, production of type 1 fimbriae, resistance to serum bactericidal activity, and modulation of intracellular host responses (IL-8, IL-1β) [ 11 , 40 , 80 , 81 , 82 , 83 , 84 , 85 ].…”
Section: Virulence and Pathogenesis Factorsmentioning
confidence: 99%
“…Among the different bacterial secretion systems, two secretion systems (type III and VI) contribute to APEC pathogenesis [ 11 , 12 ]. The regulators (EtrA and YqeI) [ 12 , 78 ] and ATPase (EivC) [ 79 ] of the type III secretion system 2 (ETT2) play a role in motility, adhesion, intracellular survival, proliferation, colonization, resistance to phagocytosis and serum bactericidal activity, expression of fimbriae genes, and the downregulation of pro-inflammatory cytokine responses. Similarly, different components of type VI secretion system, DotU (organelle trafficking protein), IcmF (intracellular multiplication factor), Hcp (hemolysis co-regulation protein), CpxR, CpxA (envelope stress response system), ClpV (ATPase), and VrgG (secreted protein) mediate interbacterial competition, adhesion, invasion, intracellular survival, colonization, motility, biofilm formation, production of type 1 fimbriae, resistance to serum bactericidal activity, and modulation of intracellular host responses (IL-8, IL-1β) [ 11 , 40 , 80 , 81 , 82 , 83 , 84 , 85 ].…”
Section: Virulence and Pathogenesis Factorsmentioning
confidence: 99%
“…Flagella are more locomotive organelles in E. coli, and critical for biofilm formation and bacterial virulence [24,25]. Several studies revealed that transcriptional regulators YqeI and ATPase EivC both influence APEC's flagella and motility [20,21], and this study supplements another transcriptional regulator in the ETT2 cluster that has an effect on APEC's flagella and motility. Serum resistance is a prerequisite for septicemia, which is a typical symptom of avian colibacillosis [26].…”
Section: Discussionmentioning
confidence: 56%
“…The sequence of the ETT2 cluster and YgeK in AE81 was obtained from whole-genome sequencing [ 21 ]. The whole-genome sequencing library was prepared by Novogene Co., Ltd.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations